Collaging illustrated mathematical word problems - Laura Caligari; Eva Norén; Paola Valero (Prometeica)
In a mathematical educational context, mathematical word problems are an established practice with the aim to connect to students’ everyday life. Drawing on Neo-material perspectives and art based research methods we explore collage as a way to critically engage with illustrated mathematical word problems. We challenge the view of mathematical knowledge production as an objective, value-neutral and disembodied process by performing agential cuts with(in) illustrated mathematical word problems from two Swedish mathematical textbooks. The perspectives and methods mobilize sensibilities that advance new points of views. Hence, contributing to broaden the range of qualitative research methods and paradigms studying mathematical word problems.